2014
DOI: 10.1016/j.neubiorev.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned taste aversion, drugs of abuse and palatability

Abstract: LIN, J.-Y., J. Arthurs and S. Reilly. Conditioned taste aversion: Palatability and drugs of abuse. NEUROSCI BIOBEHAV REV XX(x) XXX-XXX, 2014. – We consider conditioned taste aversion to involve a learned reduction in the palatability of a taste (and hence in amount consumed) based on the association that develops when a taste experience is followed by gastrointestinal malaise. The present article evaluates the well-established finding that drugs of abuse, at doses that are otherwise considered rewarding and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 206 publications
(298 reference statements)
2
63
1
8
Order By: Relevance
“…Similarly, we have recently found that anesthesia-inducing drugs (ketamine/xylazine and sodium pentobarbital) can serve as USs to support CTA learning (Lin et al, 2017a). Finally, we have discovered that drugs of abuse (e.g., amphetamine and morphine), at dose that are rewarding in other tasks (i.e., place -preference learning and self-administration tasks [e.g., Cappell & LeBlanc, 1971; Cappell, LeBlanc, & Endrenyi, 1973; Hunt & Amit, 1987; Parker, Limebeer, & Rana, 2009; Schuster & Thompson, 1969]), are capable of supporting CTA acquisition (e.g., Arthurs et al, 2012; Arthurs & Reilly, 2013; Lin, Arthurs, Amodeo & Reilly, 2012; for reviews see Lin et al, 2014, 2017b). All these findings, particularly those with drugs of abuse, are at odds with the conclusions derived from research that employed the taste reactivity test to determine palatability of the taste CS.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we have recently found that anesthesia-inducing drugs (ketamine/xylazine and sodium pentobarbital) can serve as USs to support CTA learning (Lin et al, 2017a). Finally, we have discovered that drugs of abuse (e.g., amphetamine and morphine), at dose that are rewarding in other tasks (i.e., place -preference learning and self-administration tasks [e.g., Cappell & LeBlanc, 1971; Cappell, LeBlanc, & Endrenyi, 1973; Hunt & Amit, 1987; Parker, Limebeer, & Rana, 2009; Schuster & Thompson, 1969]), are capable of supporting CTA acquisition (e.g., Arthurs et al, 2012; Arthurs & Reilly, 2013; Lin, Arthurs, Amodeo & Reilly, 2012; for reviews see Lin et al, 2014, 2017b). All these findings, particularly those with drugs of abuse, are at odds with the conclusions derived from research that employed the taste reactivity test to determine palatability of the taste CS.…”
Section: Discussionmentioning
confidence: 99%
“…En el caso de G1, al agua se le agregó resultados exitosos (Archer y Sjödén, 1979;De la Casa y Lubow, 1995;García, Kimeldorf y Koelling, 1955;Lin, Arthurs, and Reilly, 2014;Verendeev y Riley, 2012); sin embargo, no se ha probado la eficacia del CAS sobre el consumo de endulzantes naturales, como la estevia, la cual es una planta originaria del sudeste de Paraguay, conocida como "hoja dulce", que es natural como la sacarosa, tiene sabor dulce y no aporta calorías a partir de su consumo (Durán, Rodríguez, Cordón y Record, 2012).…”
Section: Solucionesunclassified
“…No obstante, en el caso de la presente investigación, las diferencias registradas en el efecto del CAS sobre el consumo de sacarosa vs. de estevia parecen recaer particularmente en las propiedades organolépti-cas de dichos endulzantes. La mayoría de los estudios previos utilizaron el CAS aplicado a sabores específicos que no contienen consecuencias postingestivas (García y Bach, 1999;Lin, Arthurs y Reilly, 2014;Verendeev y Riley, 2012). En el presente trabajo, aunque la sacarosa y el estevia tienen sabor dulce, la primera contiene calorías, y la segunda no.…”
Section: Procedimientounclassified
See 1 more Smart Citation
“…CTAs which involve associative learning between oral and visceral stimuli have been shown with rats [179][180][181][182][183][184][185]. For example, a novel taste solution (CS) followed by aversive malaise (US) will not be ingested afterward although the taste solution was rewarding before the conditioning.…”
Section: Interactions Between Oral and Visceral Sensory Signalsmentioning
confidence: 99%